The prevalence and predictors of intimate partner violence among women attending a midwife and obstetrics unit in the Western Cape - Malan, Megan (Centre for Public Mental Health, 2017)
Background: Intimate partner violence (IPV) during pregnancy is a common phenomenon across the world. The present study sought to determine the prevalence and predictors of intimate partner violence among pregnant women attending a midwife and obstetrics unit in the Western Cape. Methods: A convenience sample of a hundred and fifty pregnant women (n= 150) attending antenatal appointments at the Mitchell's Plain Midwife and Obstetrics Unit (MOU) were asked to participate in this study. Consenting women participated in an interview where they were asked questions concerning interpersonal violence and other psychosocial constructs, such as history of childhood trauma, exposure to community violence, depressive symptoms and alcohol use. Frequency distributions and descriptive statistics were calculated for categorical and continuous variables. Multivariable logistic models were developed to control for socio-demographics and psychosocial constructs. The first model was based on report of any form of IPV over the previous 12 months, while the remaining three models investigated the disaggregated forms of IPV: physical abuse, sexual abuse and emotional abuse. Results: Overall, the lifetime and 12-month prevalence rate for any IPV was 45% and 32%, respectively. For 12-month IPV, 32% reported general abuse, 29% physical and 20% reported being sexually abused. After adjusting for the effects of the other variables in the model, depressive symptoms, and reporting that this pregnancy was unplanned were significantly associated with the reporting of any IPV in the past 12 months. Looking specifically at 12 months general IPV, women who had depressive symptoms were more likely to experience some form of general IPV (OR= 6.42, CI 2.51-16.41) than women not at risk. Also, women of 'coloured' race were more likely to experience general IPV than Black African respondents (OR= 1.46, 95% CI 0.64-3.34). The model exploring associations for 12-month physical IPV found women who were at risk for depression were more likely to experience physical IPV (OR= 4.42, CI 1.88-10.41) than women not at risk, while the model exploring associations for 12-month sexual IPV found that women who reported experiencing community violence were more likely to report sexual IPV than women who reported no exposure to community violence (OR= 3.85, CI 1.14-13.08). Conclusion: This is the first study, which illustrates high prevalence rates of IPV among pregnant woman at Mitchells Plain MOU. A significant association was found between 12-month IPV and unintended pregnancy. Also, woman who are at risk for depression were found to have an increased chance of experiencing both general and physical IPV. Sexual IPV was associated with high levels of exposure to community violence. Further prospective studies in different centres are needed to address generalisability and the effect of IPV on maternal and child outcomes. Greater recognition of IPV in pregnancy could contribute to improved antenatal care, as well as enhanced policy development for appropriate intervention strategies. Key Words: Intimate partner violence; Interpersonal violence; Domestic violence; Abuse; Pregnancy; Antenatal; Postnatal depression and Community violence